Parasitic infections in germfree animals - Vieira,L.Q. (1998)
The association of vertebrate hosts with the indigenous microbiota and its effect on the response to infections has long been a subject of scientific curiosity. From the first theory supported by Louis Pasteur that life would be impossible in the absence of associated microorganisms to the development of germfree mammals for research, a lot was learned about how the normal microbiota influences the environment in which pathogens may find themselves. In the present review, we attempt to summarize the more recent results from our group and others on the influence of the normal microbiota on the outcome of parasitic infections. Our results and those of others point to a complex relationship between the mammalian system and its indigenous microbiota, leading to greater resistance to some infections and enhanced susceptibility to others